Państwo suwerenne w teorii prawa międzynarodowego Francisco de Vitorii - Wielomski, Adam (Polski Przegląd Stosunków Międzynarodowych, 2018)
The sovereign state in Francisco de Vitoria’s theory of international law Francisco de Vitoria is known as the precursor of secular international law and as the defender of the Native Peoples’ rights. The popular view is that his theory of international relations stems from the will to defend the indigenous inhabitants of the New World against the conquistadors of his native Spain. The author negates this thesis as there is no proof for this opinion. The author proves that de Vitoria created his theory of international relations before he occupied himself with the Amerindian question. His defence of the states and property of the pagan indigenous peoples stems from his earlier vision of international relations and his theory of state. Native Americans’ rights are thus “detailing" from his general theory of international relations. Also the popular thesis that his theory is of a secular nature is false, because of the Pope's role of indirect power in international relations.